Comparison of Job Stress Dimensions in Iranian Nurses with Those from other Countries Based on the Demand-Control-Support Model - Mostafa Barzideh; Alireza Choobineh; Hamidreza Tabatabaee (Shiraz University of Medical Sciences, 2014)
Background: Evidence shows that job stress potentially has adverse effect on individuals' health and organizational productivity. It has, therefore, become an important issue in the occupational health context. The aims of this study were to investigate job stress dimensions among nurses of Shiraz University of Medical Sciences (SUMS) hospitals and comparing the results with the findings of the previous studies conducted in other countries. Methods: In this cross-sectional study, 385 randomly selected nurses of SUMS participated. The Persian version of Job Content Questionnaire (P-JCQ) and demographic questionnaire were used for data collection. The linguistic validity and psychometric properties of P-JCQ have been assessed and approved in a previous study. One sample t-test was used to examine the differences between means of job stress dimension scores of the present and those of the previous studies carried out in other countries. Results: The means (SD) of decision latitude, psychological job demands, social support, physical job demands and job insecurity were found to be 58.15 (6.50), 38.19 (5.14), 22.67 (3.67), 16.03 (2.58), and 7.74 (3.85), respectively. The results revealed that decision latitude and social support dimensions were in a low level among the study subjects. In contrast, psychological job demand, physical job demand, and job insecurity dimensions were shown to be in a high level. Conclusion: The SUMS hospital environment collectively imposes higher job stress on the nurses as compared to that of other countries. To prevent harmful effects of job stress on the nurses' health and job performance, developing macro-ergonomic strategies in this working environment, such as enhancing job control, reducing job demands, and providing supportive climate, seem necessary.